Photosynthesis and Bio-Optical Properties of Fluorescent Mesophotic Corals - Ben-Zvi, Or; Wangpraseurt, Daniel; Bronstein, Omri; Eyal, Gal; Loya, Yossi (Frontiers in Marine Science, 2021)
Mesophotic coral ecosystems (MCEs) are light-dependent coral-associated communities found at 30–150 m depth. Corals inhabiting these deeper reefs are often acclimatized to a limited and blue-shifted light environment, enabling them to maintain the relationship with their photosynthetic algal symbionts (family Symbiodiniaceae) despite the seemingly suboptimal light conditions. Among others, fluorescent proteins produced by the coral host may play a role in the modulation of the quality and spectral distribution of irradiance within the coral tissue through wavelength transformation. Here we examined the bio-optical properties and photosynthetic performances of different fluorescence morphs of two mesophotic coral species Goniopora minor and Alveopora ocellata, in order to test the photosynthesis enhancement hypothesis proposed for coral fluorescence. The green morph of G. minor and the low fluorescence morph of A. ocellata exhibit, in their natural habitats, higher abundance. The morphs also presented different spectral reflectance and light attenuation within the tissue. Nevertheless, chlorophyll a fluorescence-based, and O2 evolution measurements, revealed only minor differences between the photosynthetic abilities of three fluorescence morphs of the coral G. minor and two fluorescence morphs of A. ocellata. The fluorescence morphs did not differ in their algal densities or chlorophyll concentrations and all corals harbored Symbiodiniaceae from the genus Cladocopium. Thus, despite the change in the internal light quantity and quality that corals and their symbionts experience, we found no evidence for the facilitation or enhancement of photosynthesis by wavelength transformation.